Powers of local governments in the field of security of settlements on the example of flight permits: monitoring of legislation and law enforcement practice - Ekaterina S. Shugrina (Правоприменение, 2019)
The subject. The article analyzes the conflict of norms of the current legislation, the materials of law enforcement practice in terms of establishing the powers of local governments to issue permits for flights.The purpose of the paper is to confirm or disprove hypothesis that the powers of local governments to issue permits for flights are not based on the law and are established only in by-laws.The research was carried out with use of main scientific methods (analysis, induction and deduction), special (statistical) method as well as the method of interpretation of the legal acts.The main results and scope of their application. Monitoring of legislation and law enforcement shows that local governments are more likely to be an additional barrier to business activity than a body with the necessary competence to make the appropriate decision.Local self-government bodies are empowered by a secondary normative act to issue a permit for certain actions in the airspace of the Russian Federation over populated areas. It is a question of exclusively state powers which were assigned to local governments by the will of the by-law.A number of provisions of secondary legislation regulating the peculiarities of use of airspace of the Russian Federation does not have clarity and certainty. For example, it is not clear what kind of legislation should regulate skydiving (physical culture legislation or regulation of organization of flights); hot air ballooning (is it sphere of leisure activities or organization of flights). More precise legal regulation is needed for such cases.One of the purposes of imposing the functions of flight permits on local governments is to ensure the security of the population, its life, health and safety of property. But local governments have almost no own security tools. The legislation on local self-government does not contain requirements for employees of local self-government bodies related to the availability of specialized knowledge, sufficient competence to assess the degree of risk or threat. The adoption of a significant number of municipal legal acts concerning flight permits is initiated by the transport Prosecutor's office, which considers the relevant activities of local governments as a municipal service. Analysis of law enforcement practice shows its great diversity. Some courts decide that local governments have no right to regulate the issuance of flight permits. The most numerous are court decisions when the court compels local governments to adopt administrative regulations for the provision of the relevant municipal service concerning flight permits. A certain group of court cases consists of decisions taken by the court on the basis of refusal of the claim in connection with the voluntary issuance of flight permits.Conclusions. It is shown that powers of local governments to issue permits for flights are not based on the law and are contained only in by-laws. The information possessed by the local self-government bodies can be transferred to the relevant state authorities for operational decision-making in the order of interdepartmental interaction. This power has no real impact on improving the security of residents of cities and other settlements.